Perivascular adipose tissue in vascular pathologies—a novel therapeutic target for atherosclerotic disease? - Adachi, Yusuke; Ueda, Kazutaka; Takimoto, Eiki (Frontiers in Cardiovascular Medicine, 2023)
Most blood vessels are surrounded by adipose tissues known as perivascular adipose tissue (PVAT). Emerging experimental data have implicated the potential involvement of PVAT in the pathogenesis of cardiovascular disease: PVAT might be a source of inflammatory mediators under pathological conditions such as metabolic disorders, chronic inflammation, and aging, leading to vascular pathologies, while having vasculo-protective roles in a healthy state. PVAT has been also gaining attention in human disease conditions. Recent integrative omics approaches have greatly enhanced our understanding of the molecular mechanisms underlying the diverse functions of PVAT. This review summarizes recent progress in PVAT research and discusses the potential of PVAT as a target for the treatment of atherosclerosis.